ID1 promotes hepatocellular carcinoma proliferation and confers chemoresistance to oxaliplatin by activating pentose phosphate pathway. Issue 1 (December 2017) - Yin, Xin; Tang, Bei; Li, Jing-Huan; Wang, Yan; Zhang, Lan; Xie, Xiao-Ying; Zhang, Bo-Heng; Qiu, Shuang-Jian; Wu, Wei-Zhong; Ren, Zheng-Gang
Abstract Background Drug resistance is one of the major concerns in the treatment of hepatocellular carcinoma (HCC). The aim of the present study was to determine whether aberrant high expression of the inhibitor of differentiation 1(ID1) confers oxaliplatin-resistance to HCC by activating the pentose phosphate pathway (PPP). Methods Aberrant high expression of ID1 was detected in two oxaliplatin-resistant cell lines MHCC97H–OXA(97H–OXA) and Hep3B–OXA(3B–OXA). The lentiviral shRNA or control shRNA was introduced into the two oxaliplatin-resistant cell lines. The effects of ID1 on cell proliferation, apoptosis and chemoresistance were evaluated in vitro and vivo. The molecular signaling mechanism underlying the induction of HCC proliferation and oxaliplatin resistance by ID1 was explored. The prognostic value of ID1/G6PD signaling in HCC patients was assessed using the Cancer Genome Atlas (TCGA) database. Results ID1 was upregulated in oxaliplaitin-resistant HCC cells and promoted HCC cell proliferation and oxaliplatin resistance. Silencing ID1 expression in oxaliplaitin-resistant HCC cell lines inhibited cell proliferation and sensitized oxaliplaitin-resistant cells to death. ID1 knockdown significantly decreased the expression of glucose-6-phosphate dehydrogenase (G6PD), a key enzyme of the PPP. Silencing ID1 expression blocked the activation of G6PD, decreased the production of PPP NADPH, and augmented reactive oxygen and species (ROS), thus inducing cell apoptosis. Study of the molecular mechanism showed that ID1 induced G6PD promoter transcription and activated PPP through Wnt/β-catenin/c-MYC signaling. In addition, ID1/G6PD signaling predicted unfavorable prognosis of HCC patients on the basis of TCGA. Conclusions Our study provided the first evidence that ID1 conferred oxaliplatin resistance in HCC by activating the PPP. This newly defined pathway may have important implications in the research and development of new more effective anti-cancer drugs.